Preoperative navigated transcranial magnetic stimulation and tractography in transparietal approach to the trigone of the lateral ventricle. (July 2017) - Hendrix, Philipp; Senger, Sebastian; Griessenauer, Christoph J.; Simgen, Andreas; Linsler, Stefan; Oertel, Joachim
Highlights: Combination of nTMS and DTI facilitates the identification of a parietal trajectory to the trigone. It allows for sparing of visual and motor pathways as well as cortical language areas. The acquired information encouraged the confidence of the operating surgeon. Abstract: Objective: Eloquent neural structures including white matter tracts surround the trigone of the lateral ventricle. Surgical resection of trigonal tumors via the transparietal approach may cause neurological deterioration depending on the trajectory. Methods: The authors retrospectively reviewed patients with trigonal tumors that underwent combined preoperative navigated transcranial magnetic stimulation (nTMS) and optic radiation tractography to guide a transparietal approach towards the trigone. Results: Five patients underwent preoperative nTMS motor mapping, rTMS language mapping, nTMS-derived corticospinal tract tractography, and optic radiation tractography. The information was used to select the optimal trajectory for a transparietal approach and for intraoperative neuronavigation. Four patients underwent surgical resection. None of them experienced a new permanent deficit. Conclusion: Combination of preoperative nTMS and optic radiation tractography facilitates the identification of the optimal parietal trajectory towards the trigone. It allows for sparing of visual and motor pathways as well as cortical language areas.